(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
Cancer is a major health problem around the world. Cancer treat ment depends on radiation therapy sometimes in combination with che motherapy or hormonal therapy. The treatment of cancer with radiation and chemotherapy cause several unwanted harmful side effects. Turmeric (Curcuma longa), is a type of herb widely used as a spice. Recent re searches have shown that curcumin, the active component of turmeric possesses anticancer properties. This study aimed to evaluate the effect of γ-radiation and curcumin each of them alone or combined on HepG2 cell line proliferation, p53, Her2/neu, and MMP9 gene expression, and total antioxidant capacity. HepG2 cells were exposed to γ-radiation (R), or treated with different concentrations of curcumin alone or combined with each other. The cell viability was examined by MTT assay. Gene ex pression of p53, Her2/neu, and MMP9 were evaluated by using real-time QPCR. The total antioxidant capacity (TAC) was also measured. Cur cumin or R alone or combined decreased cell viability and induced cell death in a dose-and time-dependent manner when compared to untreated group. Curcumin and R induced p53 gene expression, while reduced Her2/neu, and MMP9 expression. Furthermore, the TAC was decreased in the treated groups compared to the untreated. Conclusion: Curcumin can sensitize HepG2 cells to radiation and would potentiate the effect of radiotherapy in cancer..